Continuous splitting of carbon fibre rovings. (March 2016) - Mäder, Th; Trautmann, M; Nestler, D; Wielage, B
Carbon fibres are fabricated in bundles. A single roving contains a minimum of 1000 filaments. Certain applications demand thinner bundles or even single fibres. Single fibres can be used as tool electrodes in electrochemical machining processes. Thinner rovings are needed in sensor applications to raise the electrical resistance of the carbon fibre bundle used as strain sensor. Rovings with a lower filament count cannot be delivered by carbon fibre producers. A splitting technology is therefore needed. A continuous bundle splitting technique was developed. It uses mechanical means, liquid flow and variations in winding force and speed to separate the filaments. The impact of winding parameters and of the liquid flow on the splitting result was quantified in experiments with the developed splitting system. An automatic and continuous splitting of carbon fibre rovings was realised. Smaller bundles of carbon fibre filaments can be provided. There is a solution to satisfy the demand on finer carbon fibre rovings.